Buddhist Way of Creating “Boworn” Power for Peace in Thai Society - Muangpratab, Phra Songkran; Sikruadong, Siriwat; ผศ.ดร., พระครูสุตวรธรรมกิจ (RATANABUTH JOURNAL, 2022)
Ban, Wat, School called “Boworn” is the main organization or central unit responsible for connecting relationships, developing, making decisions, and solving problems. Palang Bowon is a source of morality, concepts, ways of thinking and values for people living together with generosity and support and leading to local reconciliation. As a result, the main foundation of “Boworn” leading to reconciliation to create peace in society has to possess 9 elements including 1) leaders, 2) morality and ethics, 3) public mind or volunteerism, 4) participation or exchange of learning together, 5) integration of multiple intelligence, 6) sufficiency economy, 7) good governance, 8) integration of creativity with local wisdom, and 9) information technology or digital learning media.